Operation of the alula as an indicator of gear change in hoverflies. - Walker, S; Thomas, A; Taylor, G (2012)
The alula is a hinged flap found at the base of the wings of most brachyceran Diptera. The alula accounts for up to 10 per cent of the total wing area in hoverflies (Syrphidae), and its hinged arrangement allows the wings to be swept back over the thorax and abdomen at rest. The alula is actuated via the third axillary sclerite, which is a component of the wing hinge that is involved in wing retraction and control. The third axillary sclerite has also been implicated in the gear change mechanism of flies. This mechanism allows rapid switching between different modes of wing kinematics, by imposing or removing contact with a mechanical stop limiting movement of the wing during the lower half of the downstroke. The alula operates in two distinct states during flight-flipped or flat-and we hypothesize that its state indicates switching between different flight modes. We used high-speed digital video of free-flying hoverflies (Eristalis tenax and Eristalis pertinax) to investigate whether flipping of the alula was associated with changes in wing and body kinematics. We found that alula state was associated with different distributions of multiple wing kinematic parameters, including stroke amplitude, stroke deviation angle, downstroke angle of incidence and timing of supination. Changes in all of these parameters have previously been linked to gear change in flies. Symmetric flipping of the alulae was associated with changes in the symmetric linear acceleration of the body, while asymmetric flipping of the alulae was associated with asymmetric angular acceleration of the body. We conclude that the wings produce less aerodynamic force when the alula is flipped, largely as a result of the accompanying changes in wing kinematics. The alula changes state at mid-downstroke, which is the point at which the gear change mechanism is known to come into effect. This transition is accompanied by changes in the other wing kinematic parameters. We therefore find that the state of the alula is linked to the same parameters as are affected by the gear change mechanism. We conclude that the state of the alula does indeed indicate the operation of different flight modes in Eristalis, and infer that a likely mechanism for these changes in flight mode is the gear change mechanism.